2007
DOI: 10.1093/eurheartj/ehm078
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-related protein 8/14 complex is released by monocytes and granulocytes at the site of coronary occlusion: a novel, early, and sensitive marker of acute coronary syndromes

Abstract: In ACS, MRP8/14 is markedly expressed at the site of coronary occlusion by invading phagocytes. The occurrence of elevated MRP8/14 in the systemic circulation prior to markers of myocardial necrosis makes it a prime candidate for the detection of unstable plaques and management of ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
160
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(190 citation statements)
references
References 33 publications
8
160
1
2
Order By: Relevance
“…These findings have implications for the clinical use of these 4 markers of plaque instability and extend both previous clinical and experimental studies (7,8,12,13,15,21 ). The exact mechanisms leading to plaque instability, plaque fissure, and plaque rupture are incompletely understood.…”
Section: Diagnostic Value Of Markers Of Plaque Instabilitysupporting
confidence: 69%
See 1 more Smart Citation
“…These findings have implications for the clinical use of these 4 markers of plaque instability and extend both previous clinical and experimental studies (7,8,12,13,15,21 ). The exact mechanisms leading to plaque instability, plaque fissure, and plaque rupture are incompletely understood.…”
Section: Diagnostic Value Of Markers Of Plaque Instabilitysupporting
confidence: 69%
“…Pilot studies suggested a possible prognostic role for MRP-8/14 in ACS patients (13,14 ). Pregnancy-associated plasma protein A (PAPP-A) is a protease mainly produced by the placenta during pregnancy, but also by fibroblasts, osteoblasts, and vascular smooth muscle cells.…”
mentioning
confidence: 99%
“…Moreover, increased S100A8/A9 expression has become a novel, early, and sensitive marker of acute coronary syndromes. [31] Hence the study on the mechanism of S100A8 mediating cerebral I/R injury is of practical value in early diagnosis and prevention of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of S100A8/A9 is associated with an early risk of acute coronary syndromes and the severity of coronary artery disease in diabetic individuals. Previous small sub-group studies also indicate that S100A8/A9 may be a marker of subclinical atherosclerosis, as its elevation in serum corresponds with intima media thickness in patients with diabetes but without any history of previous cardiovascular diseases (CVD) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin-1 (SIRT1), adiponectin and calprotectin (S100A8/A9) are characterized as factors able to modulate either the NF-κB signaling pathway or toll-like receptor 4 (TLR-4) (6-9). Furthermore, they are considered to be important elements for the molecular pathogenesis of atherosclerosis (4)(5)(6)10,11). SIRT1 is highly expressed in endothelial cells where it controls angiogenesis through a broad variety of transcriptional regulators, including p53, fork-head box O (FoxO), NF-κB, promyelocytic leukemia protein and activated receptor-γ.…”
Section: Introductionmentioning
confidence: 99%